Kedudukan Wilayah Al-Hisbah Pada Putusan Peradilan Nomor : 1083/Pdt.G/2023/Pa.Btl Tentang Sengketa Rahn dan Ijarah - Ismail, Nurmikyana; Abdul Mujib (Sekolah Tinggi Agama Islam Negeri Majene, 2023)
A judicial decision is a question from the judge that is spoken at the trial and aims to end or resolve a case or dispute between the parties involved in the trial. Through hisbah, the state uses this institution to comprehensively control socio-economic conditions for business activities and economic practices. Religious court judges must use the compilation of sharia economic law as a source of material law to resolve sharia economic disputes. The author, using the normative juridical method, systematically describes the structure and content of judicial decisions and then the basis for the judge's consideration of the position of the al-hisbah area regarding judicial decisions as well as the practice of pawning (rahn) and ijarah financing according to sharia economic law. This research uses a case research approach (Case Approach). This approach includes reviewing cases related to the main problem and then using them to make court decisions that have permanent legal force (Inkracht). Qualitative data analysis presenting data, reducing it, and drawing conclusions from it. The judge in deciding the case used several legal bases such as Presidential Instruction Number 17/DSN-MUI/IX/2000 regarding witnesses for wealthy customers who postponed payments because after being identified the defendants were not found to have any defects in carrying out their obligations, namely paying maintenance costs, etc. as stated in the details of the plaintiff's total losses. The panel of judges decides cases fairly by applying ma'rūf and nahi mungkar for the benefit of the people according to the topic, especially sharia economics.